Artificial Intelligence and Administrative Law in Modern Governance - Yeri Antoni; Fatimah Nur Fauzia; Yovan Iristian (Lex Journal: Kajian Hukum & Keadilan, 2026)
This research examines the transformative impact of Artificial Intelligence (AI) and algorithmic decision-making (ADM) on administrative law and modern governance. As governments increasingly integrate AI into public services—from welfare distribution and tax administration to law enforcement—foundational principles of administrative law, including legality, transparency, and accountability, face unprecedented challenges. The objective of this study is to analyze how existing legal doctrines adapt to the "black-box" nature of AI and to evaluate emerging global regulatory frameworks. Utilizing a descriptive-analytical methodology rooted in a comprehensive literature review of international legal scholarship and landmark case law, the study identifies a growing tension between administrative efficiency and the protection of fundamental rights. The findings suggest that while AI enhances productivity by reducing "noise" in human judgment, it risks entrenching systemic biases and eroding procedural fairness. The results highlight the necessity of "communicative accountability" and "prospective benchmarking" to maintain the rule of law. The study concludes that modern governance requires a transition from traditional human-centric oversight to integrated socio-technical regulatory models, exemplified by the EU AI Act and the lessons learned from the failures of systems like SyRI in the Netherlands and Robodebt in Australia.